Can AI Identify Cancer Subtypes from Pathology Images? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2019)
The classification of cancer has traditionally relied on the microscopic examination of tissue samples by pathologists. This morphological analysis, while fo...
Keywords: AI in Oncology; Identify; Cancer; Subtypes; Artificial Intelligence; Deep Learning; Healthcare